Functionally graded AZ91/WC nanocomposite fabricated via friction stir processing using a novel way - Akeel Subhi; Makarim Abdulkareem; Hussein Hussein (Journal of Mining and Metallurgy, Section B: Metallurgy, 2022)
In this work, functionally graded AZ91/WC nanocomposites were produced by a novel multi-stage reduction of chamber diameter method. The WC nanoparticles were packed in chambers having graduated diameters and friction stir processing was applied using tool with four-sided fluted probe. The functionally graded nanocomposites were obtained using different tool rotational speeds (830, 960 and 1160 rpm) with a constant traverse speed and plunge depth of 40 mm/min and 0.1 mm, respectively. The characteristics of the functionally graded samples and AZ91 Mg alloy were evaluated utilizing optical and scanning electron microscopes, and energy dispersive spectroscopy as well as other tests such as hardness, pin on disc wear and potentiodynamic polarization tests. The results showed that α-Mg refining and graded distribution of WC nanoparticles were enhanced with augmenting tool rotational speed. The hardness increased slightly with augmenting tool rotational speed. The results also revealed that the wear rate was decreased and corrosion resistance was improved by adding WC nanoparticles. Abrasive wear mode was the main mode of material removal during dry sliding while cracks and pits were the main features of corroded surface.